Historical Evolution of Military Cooperation between China and Pakistan: From Strategic Partnerships to All-Weather Friendship - Javid, Irum; Ali, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2024)
China and Pakistan have a long history of friendship, trust, cooperation and collaboration. China-Pakistan Economic Corridor (CPEC), is a great contemporary symbol of Pakistan China friendship. They both also have strong routs of military cooperation. The concept of “all-weather friendship” is inspected as a sign of their deep military relations, about not only strategic cooperation but also the diplomatic solidarity. This paper explores the historical background of military relations between China and Pakistan tracing its routes from strategic cooperation to the “all-weather friendship”. This research paper pays a clear understanding of the multifaceted dynamics, determining the military relations and cooperation of China and Pakistan within the framework of regional security and global geopolitics.